2016
DOI: 10.1080/10715762.2016.1241395
|View full text |Cite
|
Sign up to set email alerts
|

Phytol has antibacterial property by inducing oxidative stress response in Pseudomonas aeruginosa

Abstract: Phytol, isolated from Aster yomena, is widely distributed as a constituent of chlorophyll. In the present study, we confirmed the antibacterial activity of phytol and its mechanism inducing oxidative cell death in Pseudomonas aeruginosa. In phytol-treated cells, elevated level of intracellular reactive oxygen species (ROS) and transient NADH depletion were observed. These results demonstrated that phytol induced ROS accumulation and that the electron transport chain was involved in increase of ROS. Due to this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 41 publications
4
44
0
1
Order By: Relevance
“…On the basis of the above spectral evidences, compound 2 was identified as transphytol. The NMR data are identical to those of reported values [5] (table 1).…”
Section: Extraction and Isolationsupporting
confidence: 85%
“…On the basis of the above spectral evidences, compound 2 was identified as transphytol. The NMR data are identical to those of reported values [5] (table 1).…”
Section: Extraction and Isolationsupporting
confidence: 85%
“…Phytol (3, 7, 11, 15‐tetramethyl‐2‐hexadecen‐1‐ol), an isoprenoid isolated from chlorophyll and thus all green vegetables, is a diterpene alcohol attached to a cysteine residue in SIG1459 (Supplemental data Figure ). Phytol has been reported to have antibacterial activity against several organisms including Staphylococcus aureus, Mycobacterium tuberculosis and Pseudomonas aeruginosa . For C .…”
Section: Discussionmentioning
confidence: 99%
“…[25] For C. aeruginosa it was proposed that phytol exerts its antibacterial properties by inducing oxidative stress. [25] However, we have previously demonstrated that phytyl-cysteine compounds similar in structure to SIG1459 possess antioxidant properties and reduce oxidative stress, [26] which would contrast with BPO's antibacterial mechanism of action (oxidation and the formation of free radicals decrease C. acnes). Thus, this is an unlikely mechanism for SIG1459 and its class of compounds to confer antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…A. yomena is a perennial herb widely distributed throughout Asia that has been used in traditional medicine to treat several diseases such as cough, asthma, and insect bites (24). Several previous studies have shown that the leaf extracts or compounds of A. yomena have many pharmacological activities, including anti-microbial (25,26), antioxidant (27)(28)(29) and anti-coagulant (30) actions. Kim et al (31) showed that the phenolic compounds extracted from the leaves of this plant significantly inhibited the production of interleukin-6 by stimulating tumor necrosis factor-α in the osteoblasts, indicating an anti-inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%